Exosomal microRNA-21-5p Mediates Mesenchymal Stem Cell Paracrine Effects on Human Cardiac Tissue Contractility. Issue 7 (30th March 2018) - Mayourian, Joshua; Ceholski, Delaine K.; Gorski, Przemek A.; Mathiyalagan, Prabhu; Murphy, Jack F.; Salazar, Sophia I.; Stillitano, Francesca; Hare, Joshua M.; Sahoo, Susmita; Hajjar, Roger J.; Costa, Kevin D.
Abstract : Rationale: : The promising clinical benefits of delivering human mesenchymal stem cells (hMSCs) for treating heart disease warrant a better understanding of underlying mechanisms of action. hMSC exosomes increase myocardial contractility; however, the exosomal cargo responsible for these effects remains unresolved. Objective: : This study aims to identify lead cardioactive hMSC exosomal microRNAs to provide a mechanistic basis for optimizing future stem cell-based cardiotherapies. Methods and Results: : Integrating systems biology and human engineered cardiac tissue (hECT) technologies, partial least squares regression analysis of exosomal microRNA profiling data predicted microRNA-21-5p (miR-21-5p) levels positively correlate with contractile force and calcium handling gene expression responses in hECTs treated with conditioned media from multiple cell types. Furthermore, miR-21-5p levels were significantly elevated in hECTs treated with the exosome-enriched fraction of the hMSC secretome (hMSC-exo) versus untreated controls. This motivated experimentally testing the human-specific role of miR-21-5p in hMSC-exo–mediated increases of cardiac tissue contractility. Treating hECTs with miR-21-5p alone was sufficient to recapitulate effects observed with hMSC-exo on hECT developed force and expression of associated calcium handling genes (eg, SERCA2a and L-type calcium channel). Conversely, knockdown of miR-21-5p in hMSCs significantly diminished exosomal procontractile and associated calcium handling gene expression effects on hECTs. Western blots supported miR-21-5p effects on calcium handling gene expression at the protein level, corresponding to significantly increased calcium transient amplitude and decreased decay time constant in comparison to miR-scramble control. Mechanistically, cotreating with miR-21-5p and LY294002, a PI3K inhibitor, suppressed these effects. Finally, mathematical simulations predicted the translational capacity for miR-21-5p treatment to restore calcium handling in mature ischemic adult human cardiomyocytes. Conclusions: : miR-21-5p plays a key role in hMSC-exo–mediated effects on cardiac contractility and calcium handling, likely via PI3K signaling. These findings may open new avenues of research to harness the role of miR-21-5p in optimizing future stem cell-based cardiotherapies. Abstract : Supplemental Digital Content is available in the text.